Norms and percentile rankings of health-related fitness for fitness majors at the University of Wisconsin - La Crosse - Carlyle, Douglas Kent (My University, 1989)
This study evaluated four health-related fitness components: cardiovascular endurance, flexibility, muscular endurance, and body composition. Data were collected on a varied number of subjects for each test. The subjects were enrolled in entry level fitness classes at the University of Wisconsin - La Crosse and consisted of 132 males and 107 females between the ages of 18 and 25 years.
Keywords: Physical fitness, Wisconsin, La Crosse